Cognitive function in toddlers with congenital heart disease: The impact of a stimulating home environment. (19th November 2020) - Bonthrone, Alexandra F.; Chew, Andrew; Kelly, Christopher J.; Almedom, Leeza; Simpson, John; Victor, Suresh; Edwards, A. David; Rutherford, Mary A.; Nosarti, Chiara; Counsell, Serena J.
Abstract: Infants born with congenital heart disease (CHD) are at increased risk of neurodevelopmental difficulties in childhood. The extent to which perioperative factors, cardiac physiology, brain injury severity, socioeconomic status, and home environment influence early neurodevelopment is not clear. Sixty‐nine newborns with CHD were recruited from St Thomas' Hospital. Infants underwent presurgical magnetic resonance imaging on a 3‐Tesla scanner situated on the neonatal unit. At 22 months, children completed the Bayley Scales of Infant and Toddler Development‐3rd edition and parents completed the cognitively stimulating parenting scale to assess cognitive stimulation at home. Level of maternal education and total annual household income were also collected. Hospital records were reviewed to calculate days on the intensive care unit post‐surgery, time on bypass during surgery, and days to corrective or definitive palliative surgical intervention. In the final analysis of 56 infants, higher scores on the cognitively stimulating parenting scale were associated with higher cognitive scores at age 22 months, correcting for gestational age at birth, sex, and maternal education. There were no relationships between outcome scores and clinical factors; socioeconomic status; or brain injury severity. Supporting parents to provide a stimulating home environment for children may promote cognitive development in this high‐risk population.